Developed microbial granules containing photosynthetic pigments for carbon dioxide reduction in palm oil mill effluent. (January 2017) - Najib, M.Z.M.; Salmiati,; Ujang, Z.; Salim, M.R.; Ibrahim, Z.
Abstract: Since the photosynthetic process offers a natural way of sequestering carbon dioxide (CO2 ) from industrial wastewater treatment such as the ponding system to treat palm oil mill effluent (POME), microbial granules possessing photosynthetic pigments were developed in a sequencing batch reactor (SBR) system using POME. POME from the last pond was used as source of nutrients for the biogranulation process. The developed microbial granules had shown the potential of retaining high accumulation of biomass concentration in the reactor (6.90–8.25 g L −1 ), good settling properties (18.0–103.0 m h −1 ) and improvement in size collected ranging from 0.3 to 2.36 mm as well as physical strength at integrity coefficient of 2% with most of the granules retained in the last day were 1.4 mm. The pigment analysis indicated the presence of the bacteriochlorophyll a implying the presence of anoxygenic photosynthetic bacteria. However, it is important to note that the molecular identification of the bacteria showed the presence of Enterobacter cloacae, Bacillus cereus and Lysinibacillus sp. which are typically known to be non-photosynthetic. These bacteria were found to possess photosynthetic pigments, mainly bacteriochlorophyll a and carotenoids. Highlights: Successfully developed microbial granules with photosynthetic pigments using POME. Improve CO2 reduction using microbial granules containing photosynthetic pigments. Non-photosynthetic bacteria found in granules to possess photosynthetic pigments.